2003
DOI: 10.1046/j.1471-4159.2003.01707.x
|View full text |Cite
|
Sign up to set email alerts
|

A dual role for poly‐ADP‐ribosylation in spatial memory acquisition after traumatic brain injury in mice involving NAD+ depletion and ribosylation of 14‐3‐3γ

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) is a homeostatic enzyme that paradoxically contributes to disturbances in spatial memory acquisition after traumatic brain injury (TBI) in transgenic mice, thought to be related to depletion of its substrate nicotinamide adenine dinucleotide (NAD + ). In this study, systemic administration of the PARP-1 inhibitor 5-iodo-6-amino-1,2-benzopyrone (INH2BP) after TBI preserved brain NAD + levels and dose-dependently reduced poly-ADPribosylation 24 h after injury. While moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 49 publications
(78 reference statements)
5
106
0
2
Order By: Relevance
“…In the case of tubulin, this was initially proposed to be regulated by mono-ADP-ribosylation by cellular enzymes, although only in an in vitro analysis (32). More recently, evidence of poly-ADP-ribosylation of this protein has also been reported in mouse brain homogenates (33). However, consistent with the single narrow band seen around the expected molecular mass (Fig.…”
Section: Purification and Identification Of Substrates Of Intracellulmentioning
confidence: 78%
“…In the case of tubulin, this was initially proposed to be regulated by mono-ADP-ribosylation by cellular enzymes, although only in an in vitro analysis (32). More recently, evidence of poly-ADP-ribosylation of this protein has also been reported in mouse brain homogenates (33). However, consistent with the single narrow band seen around the expected molecular mass (Fig.…”
Section: Purification and Identification Of Substrates Of Intracellulmentioning
confidence: 78%
“…Using this assay, we were able to show an increase in CSF PAR-modified proteins and associations between male sex and increasing patient age. Increased PARP activation has been shown in multiple experimental models of TBI, including controlled cortical impact in mice and rats, and fluid percussion injury in rats (LaPlaca et al, 1998;Satchell et al, 2003;Lai et al, 2008). Importantly, a detrimental role for PARP overactivation after TBI has been shown using both PARP-1 knockout mice (B) Relationship between mean and peak CSF PAR-modified protein levels and age in TBI patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that regulated PAR metabolism is important in maintaining normal neuronal functions. Recent studies have also suggested a role for PARP-1 in learning and memory (Satchell et al 2003;CohenArmon et al 2004). Cohen-Armon et al (2004) used the marine mollusk Aplysia as a model system to examine the role of a PARP-1 homolog in long-term memory formation.…”
Section: Neuronal Functionmentioning
confidence: 99%